Analysis of weir with adjustable height as a flow measuring device a case study of La Mesa portal weirs in Quezon City - Rosete, Vince Lowel H.
Weirs are overflow structures built in open channels to measure flow rates. Weirs that do not meet the minimum requirements concerning geometry and conditions of upstream flow are classified as non-standard weirs. Analysis and calibration tests are needed for these weirs to determine the coefficient of discharge Cd for flow measurement application. This study analyzed the capability of the two non-standard weirs located in La Mesa Portal as flow measuring devices by developing equations for Cd. The La Mesa Portal in Novaliches, Quezon City is a water diversion facility with two (2) diversion channels and two (2) weirs. Considering new diversion requirements, adjustable metal plates were placed on top of the weirs. Consequently, the crest height varies, resulting in different flow characteristics at different heights. For the new configuration, an estimate of discharge was developed for modular and non-modular flow conditions. A weir equation of the form Q = Cd√2gbH1.5 was adapted. Dimensional analysis was performed to identify the relevant dimensionless parameters for Cd. Non-linear regression analysis was used to form equations predicting Cd. The accuracy of the resulting equations was gauged by comparing the computed discharge with the discharge measured covering the given weirs and the two diversion channels.